Консолидация информации о деятельности организации: системологический вербальный подход - Косило, Николай Семенович; Ельчанинов, Дмитрий Борисович; Гуца, Олег Николаевич (НТУ "ХПИ", 2015)
Рассмотрены классический и системологический подходы к определению миссии организации. Проанализированы основные этапы построения сбалансированной системы показателей деятельности предприятия на примере компании электроснабжения: формулировка миссии, описание ценностей, формирование видения будущего, выработка стратегии, определение целей (финансовых, клиентских, внутренних процессов, обучения и развития персонала организации) и показателей их достижения. Показана эффективность вербального подхода для решения этой задачи.

Classical and systemological approaches to definition of the organization mission are considered. The main stages of the enterprise balanced scorecard creation on an example of the power supply company are analyzed: mission formulation, values description, future vision formation, strategy elaboration, goals definition (financial, client, internal processes, training and development of the organization personnel) and indicators of their achievement. Formation of the company’s development strategy begins with the construction of a model corresponding to the current indicators of its activity. Each set of values of the indicators of the company corresponds to a certain model of the company.
Information consolidation about organization activity: systemological verbal approach
Keywords: сбалансированная система показателей; системология; вербальный анализ; линии электропередач; ЛЭП; balanced scorecard; systemology; verbal analysis